2015
DOI: 10.1016/j.cct.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Combining intensive practice nurse counselling or brief general practitioner advice with varenicline for smoking cessation in primary care: Study protocol of a pragmatic randomized controlled trial

Abstract: Dutch Trial Register NTR3067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The study pointed out that the main expectation of nurses is to support tobacco users in the smoking cessation process. A qualitative study conducted in the Netherlands with 14 smokers and 9 PHC health professionals showed nurses were the preferred providers of intensive behavioral support with a focus on smoking cessation (23) .…”
Section: Discussionmentioning
confidence: 99%
“…The study pointed out that the main expectation of nurses is to support tobacco users in the smoking cessation process. A qualitative study conducted in the Netherlands with 14 smokers and 9 PHC health professionals showed nurses were the preferred providers of intensive behavioral support with a focus on smoking cessation (23) .…”
Section: Discussionmentioning
confidence: 99%
“…This study was a multi-site two-group parallel randomized controlled trial evaluating intensive counselling from a PN versus usual care from a GP, both combined with openlabel varenicline for smoking cessation. A detailed description of the protocol has been published previously [19]. Ethical approval had been obtained (NL30057.068.09/ METC 09-03-075), and the study had been registered in the Dutch Trial Register (NTR3067).…”
Section: Designmentioning
confidence: 99%
“…Abstinence rates from weeks 9 to 26 were expected to be 35% in the PN group and 20% in the GP group [19]. The estimated quit rates derived from the results of previous varenicline trials when using varenicline only [11,12] and from one of our own smoking cessation trials that combined individual counselling with nortriptyline [21].…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations